2017
DOI: 10.2174/1389202918666170329110021
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Gastric Cancer Molecular Genetic Markers in Surgical Practice

Abstract: Introduction: We have investigated aberrant methylation of genes CDH1, RASSF1A, MLH1, N33, DAPK, expression of genes hTERT, MMP7, MMP9, BIRC5 (survivin), PTGS2, and activity of telomerase of 106 gastric tumor samples obtained intra-operatively and 53 gastric tumor samples from the same group of patients obtained endoscopically before surgery. Biopsy specimens obtained from 50 patients with chronic calculous cholecystitis were used as a control group. Together with tissue samples obtained from different sites r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…GC remains a heavy burden and a huge challenge to the modern society with limited effective treatments for patients at advanced stages. In the field of genetics, genetic markers and genetic molecular mechanisms accountable for the progression of GC have aroused wide concerns (Nemtsova et al, 2017;Raimondi et al, 2018;Xiao et al, 2020;Yin et al, 2020). In the present study, we reported a novel PEA3/miR-25/SIK1 axis which potentially plays crucial functions in GC progression with the possible involvement of the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 55%
“…GC remains a heavy burden and a huge challenge to the modern society with limited effective treatments for patients at advanced stages. In the field of genetics, genetic markers and genetic molecular mechanisms accountable for the progression of GC have aroused wide concerns (Nemtsova et al, 2017;Raimondi et al, 2018;Xiao et al, 2020;Yin et al, 2020). In the present study, we reported a novel PEA3/miR-25/SIK1 axis which potentially plays crucial functions in GC progression with the possible involvement of the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 55%
“…Loss of CDH1 expression appears after inactivation of both copies, where one allele can be mutant, and the second allele is inactivated by promotor methylation in approximately 50% of cases. We have previously demonstrated that CDH1 promoter methylation is associated with the diffuse Lauren type and locally advanced GC 13 . Other studies have shown the prognostic relevance of CDH1 mutations in diffuse GC, where the presence of somatic mutations in this gene was associated with a decrease in patient survival, regardless of the stage of the disease 14 .…”
Section: Discussionmentioning
confidence: 96%
“…Hypermethylation of various genes in gastric tissues is currently associated with a higher risk of tumorigenesis. Hypermethylation of CDH1 and other genes was observed in nontumor mucosa samples from GC patients [54,55].…”
Section: Mechanisms Of E-cadherin Inactivation In the Tumorsmentioning
confidence: 99%